HPV infection and intraepithelial lesions from the anal region: how to diagnose? - Carvalho,Newton Sérgio de (2011)
In the last years, the prevalence of HPV infection in the anal region has increased, especially in some groups like homosexual and HIV-positive people. Since this infection can be associated with the development of squamous anal cancer due to its progression from HPV infection to anal intraepithelial neoplasia (AIN) and finally to cancer, the screening and evaluation of these conditions are important. Anal cytology and high resolution anoscopy are good methods that are available and can be used. Although useful, these methods should be performed correctly and not indiscriminately in all patients. Patients for whom anal cytology screening is recommended are: HIV-infected patients, homosexuals, women who present with high-grade vulvar squamous intraepithelial neoplasia, vulvar cancer or cervical cancer. An abnormal anal cytology should be further evaluated with high resolution anoscopy.